Tanggung Gugat Sengketa Hak Pertanahan Terhadap Pembeli yang Beritikad Baik - Deny Pratika; Suwito; Rommy Hardyansah (ManBiz: Journal of Management and Business, 2024)
The purpose of this study is to determine the legal basis or legal considerations of the panel of judges in deciding Civil Case Number 29/Pdt.G/2023/PN.Mjk. To find out these problems, the author uses Normative Research methods, legislative approaches, scientific journals, court decisions, with Library data collection techniques, and descriptive and qualitative analysis.The result of the author's analysis is that he disagrees with the judge's consideration in deciding the case, with considerations including the existence of procedures or conditions for the legal acquisition of sale and purchase of land based on Legislation, as well as the existence of a Supreme Court Circular Letter governing Good Faith Buyers, and the absence of strict regulations governing legal protection for good faith buyers, causing multiple interpretations of existing rules and resulting in different court decisions even in the same type of case.